Richness and trophic guilds of carnivorous mammals in ejido Nuevo Becal, Calakmul, Campeche, Mexico - Briceño Méndez, Marcos; Naranjo Piñera, Eduardo; Pérez Irineo, Gabriela; Contreras Perera, Yamili Jazmin; Sandoval Serés, Lisa; Hidalgo Mihart, Mircea (2017)
The prevalent and increasing situations such as the expansion of areas for agricultural use, livestock raising and hunting represent the most complex issues for the conservation of wild species. Mammals of the Order Carnivora are key species in ecosystems because they respond differently to changes in habitat. This study explored the species richness and composition of trophic guilds of the assemblage of the Order Carnivora in an area adjacent to Calakmul Biosphere Reserve, Mexico. From February 2014 to February 2015, 10 stations with camera traps were set within the sub-evergreen tropical forest near water bodies, roads and trails. The structure of the carnivorous assemblage was evaluated through the species richness and trophic guild of species. The recording efficiency of traps was evaluated through the latency to first detection (LTD). A total of 76 photographic records were obtained for eight species of the Order Carnivora, as well as direct observations of three additional species, so the assemblage recorded was composed of 11 species. Four trophic guilds were identified: carnivores (5 species), omnivores (4), insectivores (1), and frugivores (1). The Order consists of two species of large predators (Panthera onca and Puma concolor) and three generalist species (Urocyon cinereoargenteus, Puma yagouaroundi, and Procyon lotor). P. concolor and Leopardus wiedii displayed a low LTD (<140 days-trap). The eleven species recorded represent 26 % of the species of this Order countrywise, and 64 % for the state of Campeche. According to Mexican laws, 55 % of Carnivore species are in a threatened category. The diversity of guilds was similar to other assemblages, particularly for the carnivorous and omnivorous guilds. The diversity observed in the Nuevo Becal region confirms its importance for the conservation of the Order Carnivora, and the relevance of the evaluation of wild population in areas adjacent to large reserves such as Calakmul. Situaciones prevalentes y en aumento como la expansión de áreas para uso agrícola, la ganadería y la cacería representan los mayores problemas para la conservación de especies silvestres fuera de las áreas protegidas. Los mamíferos del Orden Carnivora son importantes en los ecosistemas debido a que responden de manera distinta a cambios en el hábitat. Este estudio se enfoca en conocer la riqueza de especies y composición de gremios tróficos del ensamblaje del Orden Carnivora en un área adyacente a la Reserva de la Biosfera de Calakmul, Campeche, México. Desde febrero de 2014 a febrero de 2015, 10 estaciones con fototrampas fueron establecidas dentro de la selva mediana sub-perennifolia en sitios cercanos a cuerpos de agua, caminos y brechas. La estructura del ensamblaje de carnívoros fue evaluada por medio de la riqueza específica y del gremio trófico de las especies. La eficiencia de las trampas en el registro fue evaluada mediante el cálculo del Tiempo de Latencia para la Primera Detección (LTD). Se obtuvieron 76 registros fotográficos independientes de 8 especies del orden Carnivora, además otras tres especies más fueron avistadas, por lo que en total fueron 11 especies. Los gremios tróficos fueron cuatro: carnívoros (5 spp.), omnívoro (4 spp.), insectívoro (1sp.), y frugívoro (1sp.). El Orden estuvo integrado por dos especies de depredadores de talla grande (Panthera onca y Puma concolor) y tres especies de hábitos generalistas (Urocyon cinereoargenteus, Puma yagouaroundi y Procyon lotor). Los valores de LTD para el registro de P. concolor y Leopardus wiedii fueron los más bajos (<140 días-trampa). Las 11 especies registradas representan el 26 % de las especies de este orden a nivel nacional y el 64 % para el estado de Campeche. La diversidad de gremios fue similar a otros ensamblajes, particularmente para el gremio carnívoro y omnívoro. El 55 % de las especies se encuentra en alguna categoría de riesgo según la legislación mexicana. Esta diversidad en el ejido Nuevo Becal confirma su importancia para la conservación del orden Carnivora y la importancia de la evaluación de las poblaciones silvestres en áreas adyacentes a grandes reservas como la de Calakmul. Key words: Calakmul; camera traps; carnivore; communal areas; conservation.